HISTORISITAS DISYARI’ATKANNYA PERINTAH SALAT (Refleksi Tentang Tafsir Ayat Perintah Shalat) - Suhaimi Suhaimi (STIU Al-Mujtama Pamekasan, 2018)
Prayers are the commandments of Allah which must be fulfilled by every Muslim. Implied sin against those who do not do it, even some who declare infidels for those who leave it because of their disobedience in the prayer order. In the history of prayer the direct orders of Allah to the Prophet Muhammad. without going through an intermediary numbering five times a day. The basis of the law is the basis of the Qur'an and the traditions and traditions of the scholars. The method used in this paper is done by studying the literature related to the material of the prayer order, especially the books of tafsir, which then performed a kind of interpretation both objectively and subjective.